2008
DOI: 10.4319/lo.2008.53.4.1376
|View full text |Cite
|
Sign up to set email alerts
|

Tracing 13C‐enriched dissolved and particulate organic carbon in the bacteria‐containing coral reef sponge Halisarca caerulea: Evidence for DOM‐feeding

Abstract: Here we report on the trophodynamics of the bacteria-containing coral reef sponge Halisarca caerulea. The assimilation and respiration of the 13 C-enriched substrates glucose, algal-derived dissolved and particulate organic matter (diatom-DOM and -POM), and bacteria were followed in 1-and 6-h incubations. Except for glucose, all substrates were readily processed by the sponge, with assimilation being the major fate. 13 C-Enrichment patterns in fatty acid biomarkers revealed that sponge dissolved organic 13 C a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
134
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(146 citation statements)
references
References 42 publications
9
134
3
Order By: Relevance
“…Sponges attached to mangrove roots are in the direct vicinity of root leachates and exposed to high concentrations of tannins where tannins accumulate. The presence of tannin-degrading symbionts may provide typical mangrove sponges a competitive advantage, provided that symbionts play an important role in the assimilation of organic matter (Weisz et al, 2008;de Goeij et al, 2008a). It has been demonstrated that typical mangrove species grow more rapidly on mangrove roots compared to typical reef species (Wulff, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Sponges attached to mangrove roots are in the direct vicinity of root leachates and exposed to high concentrations of tannins where tannins accumulate. The presence of tannin-degrading symbionts may provide typical mangrove sponges a competitive advantage, provided that symbionts play an important role in the assimilation of organic matter (Weisz et al, 2008;de Goeij et al, 2008a). It has been demonstrated that typical mangrove species grow more rapidly on mangrove roots compared to typical reef species (Wulff, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…As organisms increase in size, SA/V drops and osmotrophy alone becomes insufficient to meet nutrient demands. Thus, strictly osmotrophic organisms tend to be microscopic (e.g., bacteria), although some macroscopic animals, including sponges, corals, brachiopods, bryozoans, molluscs, and echinoderms, use osmotrophic feeding on DOC as a supplemental food source (22)(23)(24)(25)(26).…”
Section: Resultsmentioning
confidence: 99%
“…In some cases, acetate was a more preferable carbon source for bacteria relative to glucose and amino acids (Guilini et al 2010). Marine invertebrates prefer fatty acids or algal-derived amino acids to glucose (Baines et al 2005, de Goeij et al 2008. It is probable that the incorporation of DOM differs substantially among organisms depending on the types of DOM available.…”
mentioning
confidence: 99%
“…The concentration of DOC in sedimentary pore water is generally higher than that in the overlying seawater by values up to an order of magnitude, although most DOC is presumably refractory (Burdige 2002). This implies that some of the labile molecular components of the DOC could be possible carbon sources for deep-sea foraminiferal species.The uptake of DOC by a number of benthic taxonomic groups, including bacteria (Cahet et al 1990, Guilini et al 2010, benthic foraminifera (DeLaca et al 1981, DeLaca 1982, marine invertebrates (Shirayama 1992, Baines et al 2005, de Goeij et al 2008, Guilini et al 2010, and whole benthic communities (Sawyer & King 1993, van Oevelen et al 2006a has been reported. However, most previous studies were limited to shallow-water organisms that can utilize relatively large amounts of organic matter produced on the ocean surface.…”
mentioning
confidence: 99%